2021
DOI: 10.1136/bmjopen-2020-043677
|View full text |Cite
|
Sign up to set email alerts
|

Association between extremely high high-density lipoprotein-cholesterol and hypertensive retinopathy: results of a cross-sectional study from Kanagawa Investigation of Total Checkup Data from the National Database-6 (KITCHEN-6)

Abstract: ObjectivesDoubt has been cast on the atheroprotective effect of very high high-density lipoprotein cholesterol (HDL-C). Hypertensive retinopathy (HR) is caused by persistent systemic hypertension. Therefore, we aimed to investigate the association between extremely high HDL-C (EH-HDL) and HR.DesignA cross-sectional study.ParticipantsA total of 4072 general Japanese population aged 40–74 years who underwent regular medical check-ups including fundus examinations.Outcome measuresHR and clinical parameters includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…A meta-analysis by Wang et al 72 showed a significantly positive association between HDL-C and AMD, suggesting people with high HDL-C levels may be at an increased risk for AMD. In addition to AMD, HDL-C is also significantly associated with hypertensive retinopathy, 36 suggesting extremely high HDL reflects a specific atherosclerotic condition. A plausible explanation for this discrepancy is that HDL-C can be modified via myeloperoxidase-associated mechanisms under certain conditions, thus losing its protective effect and becoming atherogenic.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Wang et al 72 showed a significantly positive association between HDL-C and AMD, suggesting people with high HDL-C levels may be at an increased risk for AMD. In addition to AMD, HDL-C is also significantly associated with hypertensive retinopathy, 36 suggesting extremely high HDL reflects a specific atherosclerotic condition. A plausible explanation for this discrepancy is that HDL-C can be modified via myeloperoxidase-associated mechanisms under certain conditions, thus losing its protective effect and becoming atherogenic.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, we have demonstrated the association of extremely high HDL-C, mostly defined as > 100 mg/dL, with diabetes [17], high blood pressure [18], and hypertensive retinopathy [31]. All of these are well-known risk factors for the incidence of kidney disease and proteinuria [1,2,4].…”
Section: Discussionmentioning
confidence: 99%
“…To date, three studies addressed the association between HDL-C concentration and hypertension [ 22 , 23 , 24 ]. Additionally, we recently showed an association between extremely high HDL-C (≥110 mg/dL) and hypertensive retinopathy in a general population who underwent fundus examinations [ 25 ]. Our results suggested a positive association between HDL-C concentration and blood pressure/hypertension-related pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggested a positive association between HDL-C concentration and blood pressure/hypertension-related pathology. However, these four studies [ 22 , 23 , 24 , 25 ], which examined the pathophysiology of very low and high HDL-C concentrations (e.g., <30 mg/dL and ≥90 mg/dL), consisted of relatively small sample sizes (<5000 participants in total). Actually, the number of subjects with hypertensive retinopathy was only 16 in the extremely high HDL-C group in our previous study [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation